Vascular dysfunction and increased cardiovascular risk in hypospadias. (17th March 2022) - Lucas-Herald, Angela K; Montezano, Augusto C; Alves-Lopes, Rheure; Haddow, Laura; Alimussina, Malika; O'Toole, Stuart; Flett, Martyn; Lee, Boma; Amjad, S Basith; Steven, Mairi; Brooksbank, Katriona; McCallum, Linsay; et al.
Abstract: Aims: Hypogonadism is associated with cardiovascular disease. However, the cardiovascular impact of hypogonadism during development is unknown. Using hypospadias as a surrogate of hypogonadism, we investigated whether hypospadias is associated with vascular dysfunction and is a risk factor for cardiovascular disease. Methods and results: Our human study spanned molecular mechanistic to epidemiological investigations. Clinical vascular phenotyping was performed in adolescents with hypospadias and controls. Small subcutaneous arteries from penile skin from boys undergoing hypospadias repair and controls were isolated and functional studies were assessed by myography. Vascular smooth muscle cells were used to assess: Rho kinase, reactive oxygen species (ROS), nitric oxide synthase/nitric oxide, and DNA damage. Systemic oxidative stress was assessed in plasma and urine. Hospital episode data compared men with a history of hypospadias vs. controls. In adolescents with hypospadias, systolic blood pressure ( P = 0.005), pulse pressure ( P = 0.03), and carotid intima-media thickness standard deviation scores ( P = 0.01) were increased. Arteries from boys with hypospadias demonstrated increased U46619-induced vasoconstriction ( P = 0.009) and reduced acetylcholine-induced endothelium-dependent ( P < 0.0001) and sodium nitroprusside-induced endothelium-independent vasorelaxation ( P < 0.0001). Men born with hypospadias were at increased risk of arrhythmia [odds ratio (OR) 2.8, 95% confidence interval (CI) 1.4–5.6, P = 0.003]; hypertension (OR 4.2, 95% CI 1.5–11.9, P = 0.04); and heart failure (OR 1.9, 95% CI 1.7–114.3, P = 0.02). Conclusion: Hypospadias is associated with vascular dysfunction and predisposes to hypertension and cardiovascular disease in adulthood. Underlying mechanisms involve perturbed Rho kinase- and Nox5/ROS-dependent signalling. Our novel findings delineate molecular mechanisms of vascular injury in hypogonadism, and identify hypospadias as a cardiovascular risk factor in males. Structured Graphical Abstract: